Semiconductor device

CN116525556BActive Publication Date: 2026-10-30KYOCERA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310091754.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-01-31
Filing Date
2023-01-30
Publication Date
2026-10-30
Estimated Expiration
2043-01-30

AI Technical Summary

Benefits of technology

[0031]根据本发明能够提供一种半导体装置,其具有能使用高输出且线宽窄的激光进行视觉识别性良好的标记的密封材料(树脂组合物的固化物)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116525556B_ABST
    Figure CN116525556B_ABST
Patent Text Reader

Abstract

A semiconductor device has a substrate, a semiconductor element mounted on the substrate, and a cured product of a resin composition sealing the semiconductor element, the resin composition containing a thermosetting resin, a curing agent, and an inorganic filler, wherein when the reflectance of the surface of the cured product at a wavelength λ is denoted by R0, the chromaticity coordinates measured are denoted by (L0, a0, b0), when laser processing is performed with a laser wavelength of 532 nm, the reflectance of the laser-processed position at the wavelength λ is denoted by R1, and the chromaticity coordinates of the laser-processed position measured are denoted by (L1, a1, b1), the following formulas (1) to (3) are satisfied. R1 ≥ -0.0050 × λ + 9.3 (450 ≤ λ ≤ 600) (1); R0 ≤ -0.0047 × λ + 7.6 (450 ≤ λ ≤ 600) (2); |b1 - b0| ≤ 0.45 (3). * 0, a * 0, b * 0 * 1, a * 1, b * 1 * 1 - b * 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a semiconductor device having a substrate, a semiconductor element mounted on the substrate, and a cured resin composition sealing the semiconductor element. Background Technology

[0002] Traditionally, in semiconductor devices, product names and other markings have been made by irradiating the surface of a cured resin composition that seals a semiconductor with a laser.

[0003] For example, Patent Document 1 discloses a sealing resin composition intended to improve the visual recognition of laser embossing, which contains epoxy resin, a curing agent, inorganic filler, and black titanium dioxide. The cured product of this sealing resin composition has an L... * a * b * In the color coordinate system, brightness L * Values ​​range from 29.0 to 33.5, a * Values ​​range from -2.0 to -0.1, b * The value ranges from -5.0 to -2.5. Furthermore, Patent Document 1 discloses an electronic device comprising electronic components and a sealing material for sealing the electronic components, wherein the sealing material is a cured product of the aforementioned sealing resin composition. In Patent Document 1, the sealing material is marked using a laser with a wavelength of 1090 nm.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-132750. Summary of the Invention

[0007] In recent years, high-output lasers such as green lasers (wavelength 532nm) have been used for laser marking. When using this high-output (short wavelength) laser for laser marking, the laser linewidth can be narrowed, and the marking can be completed clearly.

[0008] However, narrowing the laser linewidth reduces visual recognition, and simply setting the range of color coordinates of the sealing material (cured product) as in Patent Document 1 is insufficient to ensure visual recognition. In particular, when marking QR codes (registered trademarks), a semiconductor device is needed that seals the semiconductor with a sealing material (cured resin composition) that provides clear contrast even when using high-output lasers such as green lasers.

[0009] The present invention provides a semiconductor device having a sealing material (cured resin composition) capable of marking with excellent visual recognition using a high-output laser with a narrow linewidth.

[0010] The inventors have discovered that a sealing material (cured material) having a specific relationship between the reflectivity and color coordinates of the laser-irradiated location and the reflectivity and color coordinates of the unirradiated location can solve the above-mentioned problem.

[0011] That is, the present invention is as follows.

[0012] [1] A semiconductor device comprising a substrate, a semiconductor element mounted on the substrate, and a cured resin composition sealing the semiconductor element.

[0013] The resin composition comprises (A) a thermosetting resin, (B) a curing agent, and (C) an inorganic filler.

[0014] The reflectivity of the surface of the solidified material under wavelength λ is denoted as R0.

[0015] The colorimetric coordinates of the cured material, determined according to JIS Z8781-4 (2013), were marked as (L... * 0, a * 0, b * 0)

[0016] When the solidified material is laser-processed with a laser wavelength of 532nm, the reflectivity of the laser-processed location under the wavelength λ condition is denoted as R1.

[0017] When laser processing is performed on the cured material using a laser wavelength of 532 nm, the laser processing position is marked according to the colorimetric coordinates determined by JIS Z8781-4 (2013) (L * 1, a * 1, b * 1) At that time,

[0018] The following equations (1) to (3) are satisfied.

[0019] R1≥-0.0050×λ+9.3(450≤λ≤600)··· (1)

[0020] R0≤-0.0047×λ+7.6(450≤λ≤600)··· (2)

[0021] │b * 1-b * 0│≤0.45··· (3)

[0022] [2] The semiconductor device as described in [1] above, wherein the following equations (4) to (6) are satisfied.

[0023] R1≥-0.0046×λ+9.1(500≤λ≤780)··· (4)

[0024] R0≤-0.0025×λ+6.5(500≤λ≤780)··· (5)

[0025] │a * 1-a * 0│≤0.35··· (6)

[0026] [3] The semiconductor device as described in [1] or [2] above, wherein the reflectivity R1 is 6.5 to 8.0%.

[0027] [4] The semiconductor device as described in any one of [1] to [3] above, wherein the colorimetric coordinates of the composition (y) consisting only of (A) a thermosetting resin and (B) a curing agent in the resin composition are marked as (L) according to JIS Z8781-4 (2013). * 2, a * 2, b * When 2), the following equations (7) and (8) are satisfied.

[0028] │a * 2│≤0.40···· (7)

[0029] │b * 2│≤10.00··· (8)

[0030] (wherein, the chromaticity coordinates (L) of the composition (y) * 2, a * 2, b * 2) Indicates: For cured products formed by melting and cooling each of the raw materials classified as (A) thermosetting resin and (B) curing agent, the chromaticity coordinates (L) are determined according to JIS Z8781-4 (2013). * raw a * raw b * raw ), and according to the mass ratio of each raw material contained in the composition (y), the chromaticity coordinates (L) are determined. * raw a * raw b * raw The chromaticity coordinates are obtained by weighted averaging.

[0031] According to the present invention, a semiconductor device is provided having a sealing material (cured resin composition) capable of visually recognizable marking using a high-output laser with a narrow linewidth. Attached Figure Description

[0032] Figure 1This is a diagram illustrating the contents of equations (1) and (2).

[0033] Figure 2 This is a diagram illustrating the contents of equations (4) and (5).

[0034] Figure 3 This is a cross-sectional view illustrating an example of the configuration of the semiconductor device of the present invention.

[0035] Figure 4 This is a graph showing the reflectance R1 (%) of the laser-irradiated position in the test pieces of the embodiments and comparative examples under wavelength conditions in the range of 400-800 nm.

[0036] Figure 5 This is a graph showing the reflectance R0 (%) of the un-laser-irradiated areas in the test pieces of the embodiments and comparative examples under wavelength conditions in the range of 400-800 nm.

[0037] The annotations in the attached figures are explained as follows:

[0038] 1. Semiconductor components

[0039] 2. Sealing material

[0040] 3 bumps

[0041] 4 substrate

[0042] 5. Solder balls. Detailed Implementation

[0043] The present invention will now be described in detail with reference to one embodiment.

[0044] The semiconductor device of this embodiment includes a substrate, a semiconductor element mounted on the substrate, and a cured form of a resin composition that seals the semiconductor element.

[0045] The resin composition comprises (A) a thermosetting resin, (B) a curing agent, and (C) an inorganic filler.

[0046] The reflectivity of the surface of the solidified material under wavelength λ is denoted as R0.

[0047] The colorimetric coordinates of the cured material, determined according to JIS Z8781-4 (2013), were marked as (L... * 0, a * 0, b * 0)

[0048] When the solidified material is laser-processed with a laser wavelength of 532nm, the reflectivity of the laser-processed location under the wavelength λ condition is denoted as R1.

[0049] When laser processing is performed on the cured material using a laser wavelength of 532 nm, the laser processing position is marked according to the colorimetric coordinates determined by JIS Z8781-4 (2013) (L * 1, a * 1, b * 1) At that time,

[0050] The following equations (1) to (3) are satisfied.

[0051] R1≥-0.0050×λ+9.3(450≤λ≤600) ··· (1)

[0052] R0≤-0.0047×λ+7.6(450≤λ≤600) ··· (2)

[0053] │b * 1-b * 0│≤0.45··· (3)

[0054] <Resin Composition>

[0055] The resin composition of this embodiment comprises (A) a thermosetting resin, (B) a curing agent and (C) an inorganic filler.

[0056] (A) Thermosetting resin

[0057] In this embodiment, the thermosetting resin (A) can be any thermosetting resin, and there are no particular limitations on its molecular weight, molecular structure, etc. Examples of thermosetting resin (A) include epoxy resin, imide resin, and acrylic resin. From the viewpoint of shrinkage, epoxy resin is preferred.

[0058] Epoxy resins only need to have two or more epoxy groups in one molecule, and there are no special restrictions on their molecular weight and molecular structure.

[0059] Examples of epoxy resins include, for instance, biphenyl-type epoxy resins, biphenyl phenolic varnish-type epoxy resins, cresol-type epoxy resins, cresol phenolic varnish-type epoxy resins, phenol phenolic varnish-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol S-type epoxy resins, dicyclopentadiene-type epoxy resins, triphenylmethane-type epoxy resins, heterocyclic epoxy resins containing a triazine backbone, stilbene-type difunctional epoxy resins, naphthalene-type epoxy resins, fused-ring aromatic hydrocarbon-modified epoxy resins, alicyclic epoxy resins, and polyfunctional epoxy resins. Among these, biphenyl-type epoxy resins, naphthalene-type epoxy resins, and polyfunctional epoxy resins are possible.

[0060] These epoxy resins can be used in one or in combination of two or more.

[0061] From the viewpoint of the operability of the resin composition and the melt viscosity during molding, the softening point of epoxy resin can be 40-130℃, 50-110℃, or 80-110℃.

[0062] It should be noted that the softening point in this instruction manual refers to the "ring and ball softening point", which is a value determined according to ASTM D36.

[0063] Commercially available epoxy resins include, for example, Mitsubishi Chemical Corporation's YX-4000 (epoxy equivalent 185, softening point 105℃), Mitsubishi Chemical Corporation's YX-4000H (epoxy equivalent 193, softening point 105℃), Mitsubishi Chemical Corporation's YX-4000HK (epoxy equivalent 180, softening point 107℃), Nippon Kayaku Co., Ltd.'s NC-3000 (epoxy equivalent 273, softening point 58℃), Nippon Kayaku Co., Ltd.'s NC-3000H (epoxy equivalent 288, softening point 91℃), Nippon Kayaku Co., Ltd.'s EPPN-502H (epoxy equivalent 168, softening point 67℃), and DIC Co., Ltd.'s N-655EXP-S (epoxy equivalent 200, softening point 55℃) (all of these are trade names).

[0064] The content of (A) thermosetting resin relative to the total amount of the resin composition can be 2 to 20% by mass, 4 to 15% by mass, or 7 to 13% by mass. When the content of (A) thermosetting resin is 2% by mass or more, the molding of the cured product becomes possible, and when the content of (A) thermosetting resin is 20% by mass or less, sufficient elastic modulus can be obtained.

[0065] When the thermosetting resin is epoxy resin, the epoxy resin content relative to the total amount of the resin composition can be 2 to 20% by mass, 4 to 15% by mass, or 7 to 13% by mass. When the epoxy resin content is 2% by mass or more, molding of the cured product becomes possible, and when the epoxy resin content is 20% by mass or less, sufficient elastic modulus can be obtained.

[0066] (B) Curing agent

[0067] The curing agent (B) used in this embodiment is a curing agent that can cure the thermosetting resin (A). Any curing agent that is commonly used as a sealing material for electronic components can be used without particular restrictions.

[0068] (B) The curing agent may contain a phenolic curing agent. From the viewpoint of balancing flame retardancy, moisture resistance, electrical properties, curing properties, and storage stability, a phenolic curing agent is preferred. A phenolic curing agent is a curing agent that has two or more phenolic hydroxyl groups per molecule and is capable of curing the resin containing component (A) above.

[0069] Examples of phenolic resin curing agents include phenolic varnish resins, cresol phenolic varnish resins, aralkyl-type phenolic resins, biphenyl aralkyl-type phenolic resins, naphthalene-type phenolic resins, cyclopentadiene-type phenolic resins, and triphenol alkyl-type phenolic resins. Among these, biphenyl aralkyl-type phenolic resins are particularly suitable from the viewpoint of being able to appropriately adjust the flowability during molding and easily improve the filling properties of inorganic fillers such as component (D). These can be used individually or in combination of two or more.

[0070] Other types of curing agents besides phenolic curing agents include (B) curing agents, such as amine curing agents, acid anhydride curing agents, thiol curing agents, and catalyst-type curing agents.

[0071] Examples of amine-based curing agents include aliphatic polyamines and aromatic polyamines.

[0072] Examples of anhydride-based curing agents include alicyclic anhydrides such as hexahydrophthalic anhydride (HHPA) and methyltetrahydrophthalic anhydride (MTHPA), and aromatic anhydrides such as trimellitic anhydride (TMA), pyromellitic tetracarboxylic anhydride (PMDA), and benzophenone tetracarboxylic dianhydride (BTDA).

[0073] Examples of thiol-based curing agents include polysulfides, thioesters, and thioethers.

[0074] Examples of catalyst-type curing agents include tertiary amine compounds such as benzyl dimethylamine (BDMA) and 2,4,6-tris(dimethylamino)methylphenol; imidazole compounds such as 2-methylimidazole and 2-ethyl-4-methylimidazole; and Lewis acids such as BF3 complexes.

[0075] (B) The content of the curing agent can be 0.5 to 15% by mass of the total resin composition, or 2 to 10% by mass. When the content of the curing agent (B) is more than 0.5% by mass of the total resin composition, the moldability and adhesion are good. When the content of the curing agent (B) is less than 15% by mass, sufficient elastic modulus can be obtained.

[0076] (D) Curing accelerator

[0077] The curing accelerator (D) used in this embodiment can be used without particular restriction as long as it is a curing accelerator that is commonly used as a curing accelerator for the thermosetting resin (A), which is a component of the resin composition.

[0078] Examples of (D) curing accelerators include, for instance, cycloamidinium compounds such as 1,8-diazacyclic[5.4.0]undecene-7, 1,5-diazacyclic[4.3.0]nonene-5, and 5,6-dibutylamino-1,8-diazabicyclo[5.4.0]undecene-7; these cycloamidinium compounds are then combined with quinone compounds such as maleic anhydride, 1,4-benzoquinone, 2,5-toluenequinone, 1,4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, and phenyl-1,4-benzoquinone, as well as diazobenzene. Compounds with intramolecular polarization formed by the addition of compounds with π bonds, such as methane and phenolic resins; tertiary amine compounds such as benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol, and their derivatives; 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, 2-heptadecylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,4-diamino-6-[2'-methylimidazole-(1')]-ethyl Imidazole compounds and their derivatives, including triazine compounds containing a diamino-s-silicon ring such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine and 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine; organophosphorus compounds such as tributylphosphine, methyldiphenylphosphine, triphenylphosphine, tri(4-methylphenyl)phosphine, diphenylphosphine, and phenylphosphine; and organophosphorus compounds such as maleic anhydride, 1,4-benzoquinone, 2,5-toluenequinone, and 1, Phosphorus compounds with intramolecular polarization are formed by the addition of quinone compounds such as 4-naphthoquinone, 2,3-dimethylbenzoquinone, 2,6-dimethylbenzoquinone, 2,3-dimethoxy-5-methyl-1,4-benzoquinone, and phenyl-1,4-benzoquinone, as well as compounds with π bonds such as diazonium benzene and phenolic resins; tetrasubstituted phosphonium-tetrasubstituted borates such as tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium ethyl triphenylborate, and tetrabutylphosphonium tetrabutylborate; tetraphenylborates such as 2-ethyl-4-methylimidazolium-tetraphenylborate and N-methylmorpholine-tetraphenylborate, and their derivatives. (D) Curing accelerators can be used alone or in combination with two or more.

[0079] From a flowability perspective, (D) curing accelerators can be imidazole-based curing accelerators.

[0080] The content of (D) curing accelerator relative to the total amount of resin composition can be 0.08 to 3.00% by mass, or 0.10 to 1.00% by mass. When the content of (D) curing accelerator is 0.08% by mass or more, a curing promotion effect can be obtained, and when the content of (D) curing accelerator is 3.00% by mass or less, good filling properties can be achieved.

[0081] [(C) Inorganic packing]

[0082] The inorganic filler (C) used in this embodiment can be any inorganic filler commonly used in resin compositions without particular limitations. Specifically, as the inorganic filler (C), powders such as fused silica, crystalline silica, alumina, zircon, calcium silicate, calcium carbonate, potassium titanate, barium titanate, silicon carbide, silicon nitride, aluminum nitride, boron nitride, beryllium oxide, zirconium oxide, forsterite, block talc, spinel, mullite, and titanium dioxide, as well as beads formed by spherizing these, single-crystal fibers, and glass fibers can be used. One type of inorganic filler (C) can be used, or two or more types can be used in combination.

[0083] From the perspective of improving mechanical strength, (C) inorganic filler can be fused silica or crystalline silica. From the perspective of improving thermal conductivity, (C) inorganic filler can be alumina; from the perspective of improving dielectric constant, it can be barium titanate.

[0084] (C) The average particle size of the inorganic filler can be 1–25 μm, 3–20 μm, or 3–18 μm. When the average particle size of (C) the inorganic filler is 1 μm or more, it can improve the filling properties of the resin composition; when it is 25 μm or less, it can improve the narrow portion filling properties of the resin composition. Here, average particle size refers to the overall average particle size of the inorganic fillers when multiple inorganic fillers are combined.

[0085] It should be noted that the average particle size in this embodiment refers to the particle size (D50) that accumulates to 50% from the smallest diameter side in the particle size distribution of the volume reference obtained using a laser diffraction scattering particle size distribution measuring device.

[0086] From the perspective of improving fluidity, (C) the inorganic filler can be spherical in shape.

[0087] The content of (C) inorganic filler relative to the total amount of the resin composition can be 70-95% by mass, 75-95% by mass, 77-90% by mass, or 78-90% by mass. When the content of (C) inorganic filler is 70% by mass or more, the elastic modulus of the cured resin composition can be maintained at a high level, and when the content of (C) inorganic filler is 95% by mass or less, the moldability can be improved.

[0088] [Other ingredients]

[0089] In addition to the components mentioned above, the resin composition of this embodiment may also be formulated with additives such as flame retardants, carbon black, titanium black, organic dyes, titanium dioxide, iron oxide red and other colorants, release agents, silane coupling agents and other coupling agents, ion scavengers, carnauba wax and other waxes, as needed.

[0090] When the resin composition of this embodiment contains the above-mentioned additives, the amount of each additive relative to the total amount of each resin composition can be 0.01 to 3.00% by mass, or 0.1 to 1.2% by mass.

[0091] In the resin composition of this embodiment, the content of the above-mentioned components (A) to (D) can be 80% by mass or more, 90% by mass or more, or 95% by mass or more.

[0092] [Physical properties of the resin composition]

[0093] The spiral flow value of this resin composition can be 100–300 cm. When it is above 100 cm, sufficient fluidity can be obtained during molding, and when it is below 300 cm, burrs can be reduced. From this point of view, the spiral flow value can be 150–250 cm.

[0094] The gel time of this resin composition can be 50–80 seconds. Within this range, a suitable curing time is obtained, which is suitable for productivity. From this perspective, the gel time can be 60–70 seconds.

[0095] From a manufacturing point of view, the flow viscosity of the resin composition can be 3 to 20 Pa·s, or 5 to 10 Pa·s.

[0096] The colorimetric coordinates (y) of the composition consisting only of (A) a thermosetting resin and (B) a curing agent in the resin composition, determined according to JIS Z8781-4 (2013), are marked as (L). * 2, a * 2, b * When 2), the following equations (7) and (8) can be satisfied.

[0097] │a * 2│≤0.40··· (7)

[0098] │b * 2│≤10.00··· (8)

[0099] (wherein, the chromaticity coordinates (L) of the composition (y) * 2, a * 2, b* 2) Indicates: For cured products formed by melting and cooling each of the raw materials classified as (A) thermosetting resin and (B) curing agent, the chromaticity coordinates (L) are determined according to JIS Z8781-4 (2013). * raw a * raw b * raw ), and according to the mass ratio of each raw material contained in the composition (y), the chromaticity coordinates (L) are determined. * raw a * raw b * raw The chromaticity coordinates are obtained by weighted averaging.

[0100] Alternatively, the following equation (9) can be satisfied.

[0101] │L * 2│≥50···· (9)

[0102] When |a * When 2│ is below 0.40, the influence of the cured product's color shifting towards the red direction can be significantly reduced. From this perspective, │a * 2│ can be below 0.30 or below 0.20.

[0103] When |b * When 2│ is below 11.0, the influence of the cured product's color shifting towards blue can be significantly reduced. From this perspective, │b * 2│ can be below 10.5 or below 10.0.

[0104] When |L * When the value of 2 is above 50, the reflectivity of the solidified material becomes sufficiently high.

[0105] It should be noted that by selecting light-colored (nearly colorless) resins, especially light-colored curing agents, one can achieve the desired effect. * The value of 2│ tends to decrease, and this is achieved by using a curing agent with strong color, especially a red tone, which has │a * The value of 2| tends to increase. Additionally, by selecting light-colored (nearly colorless) resins, especially light-colored epoxy resins, the value of |b is increased. * The value of 2| tends to decrease, and this is achieved by using a curing agent with strong color, especially a yellow tone, which has a tendency to reduce the value of 2|b. * The value of 2| tends to increase. Furthermore, by selecting resins with bright colors, especially bright-colored epoxy resins, the value of │L is increased. *The tendency for the value of 2| to decrease can be mitigated by selecting dark-colored resins, especially dark-colored curing agents, which exhibit |L * The value of 2│ tends to increase.

[0106] <Preparation of Resin Compositions>

[0107] When preparing the resin composition of the present invention, it can be prepared by premixing various components such as (A) thermosetting resin, (B) curing agent, (C) inorganic filler and (D) curing accelerator and said additives in a mixer or the like, then performing a kneading process in a disperser, kneader, three-roll mill or the like, followed by cooling, curing and crushing into appropriate size.

[0108] The above-mentioned pulverizing method has no particular limitations and can be used with a general pulverizer.

[0109] As a crusher, it can be used as a cutting and grinding mill, ball mill, cyclone mill, hammer mill, vibratory mill, shredder, grinder, and high-speed mill.

[0110] The resin composition of the present invention can be processed into tablets, powders, flakes, etc., depending on the molding method.

[0111] The method for manufacturing a tablet-shaped resin composition includes a step of pressing the obtained resin composition to form a tablet. Examples of methods for forming a tablet include inserting the resin composition into a mold of a size conforming to customer requirements and then compressing it using a compression molding machine at a compression rate of 80-95%.

[0112] In the method for manufacturing granular resin compositions, the granules obtained in the above-mentioned pulverizing process can be obtained by a grading process, such as sieving or air classification, to adjust the pulverized material into a particle aggregate with a specified particle size distribution. For example, a sieve of about 7 to 500 mesh is used for grading.

[0113] In methods for manufacturing sheet-like resin compositions, it is possible to obtain them by film formation after diluting the resin composition with a solvent. For example, it is possible to obtain them by removing the solvent from a coating film obtained from a resin composition diluted with a coating solvent.

[0114] By forming it into a sheet, for example, it can be made into a single sheet or a roll that can be wound up.

[0115] <Cure of Resin Composition>

[0116] The cured product is the cured product of the aforementioned resin composition.

[0117] In the solidified material,

[0118] When the solidified material is laser-processed with a laser wavelength of 532nm, the reflectivity of the laser-processed location is denoted as R1.

[0119] When laser processing is performed on the cured material using a laser wavelength of 532 nm, the laser processing position is marked with colorimetric coordinates determined according to JIS Z8781-4 (2013) (L * 1, a * 1, b * 1) At that time,

[0120] The following equations (1) to (3) are satisfied.

[0121] R1≥-0.0050×λ+9.3(450≤λ≤600) ··· (1)

[0122] R0≤-0.0047×λ+7.6(450≤λ≤600) ··· (2)

[0123] │b * 1-b * 0│≤0.45··· (3)

[0124] By satisfying the above equations (1) to (3), a high-output laser with a narrow linewidth can be used to mark the solidified material with excellent visual recognition.

[0125] The reason why visual recognition is improved when all of equations (1) to (3) are satisfied is not yet clear, but it is speculated as follows.

[0126] In this regard, the following equations (1A), (1B) and... Figure 1 To illustrate.

[0127] Equation (1A) transforms equation (1) into an equation and changes R1 to R. Similarly, equation (2A) transforms equation (2) into an equation and changes R0 to R. Furthermore, when equations (1A) and (2A) are shown in the figure, as follows... Figure 1 As shown.

[0128] R=-0.0050×λ+9.3(450≤λ≤600)···(1A)

[0129] R=-0.0047×λ+7.6(450≤λ≤600)···(2A)

[0130] The following is a speculation: Figure 1As shown, in the region with wavelength λ of 450–600 nm, i.e., the region from blue to yellow, by making the reflectivity R1 of the laser-processed position show a straight line or a higher value as in Equation (1A), and making the reflectivity R0 of the unprocessed position show a straight line or a lower value as in Equation (2A), the yellow wavelength of the laser-processed position is enhanced, thereby improving the visual recognition of the laser-processed position.

[0131] In addition, b * Corresponding to the position between yellow and blue, negative values ​​correspond to a bias towards blue, and positive values ​​correspond to a bias towards yellow. Since this invention satisfies the above equation (3), the laser processing position b... * (b * 1) b at the location not laser-processed * (b * The difference of 0)(│b * 1-b * 0│) small. Therefore, it is speculated that the enhancement of the yellow wavelength at the laser processing position caused by satisfying equations (1) and (2) is affected by b. * The difference (│b * 1-b * The visual recognition is improved due to the influence of 0│).

[0132] Based on the above viewpoints, b * The difference (│b * 1-b * 0│) can be below 0.30, below 0.25, below 0.20, or below 0.15.

[0133] It should be noted that in the range of 450≤λ≤600, using a combination of resins with high brightness tends to decrease the R1 value, while using resins with moderate brightness (specifically, L) * Combinations of resins with a content of approximately 60 or less tend to have an increasing R1 value. Furthermore, in the range of 450 ≤ λ ≤ 600, increasing the amount of colorant tends to decrease the R0 value, while decreasing the amount of colorant tends to increase the R0 value. Additionally, the brightness L of the combined raw materials themselves... * For components between approximately 50 and 60, there is a tendency for the value of R1 minus R0 (R1-R0) to decrease; outside this range, there is a tendency for the value of R1 minus R0 (R1-R0) to increase. This is achieved by decreasing b. * The absolute value of 2, having the value of b * The difference (│b * 1-b * The tendency of 0│) to decrease, by increasing b * The absolute value of 2, having the value of b * The difference (│b* 1-b * 0│) tends to increase.

[0134] The solidified material preferably satisfies one or more of the following formulas (4) to (6), more preferably two or more, and even more preferably all three.

[0135] R1≥-0.0046×λ+9.1(500≤λ≤780)··· (4)

[0136] R0≤-0.0025×λ+6.5(500≤λ≤780)··· (5)

[0137] │a * 1-a * 0│≤0.35··· (6)

[0138] The reason why visual recognition is improved when equations (4) to (6) are satisfied is not yet clear, but it is speculated as follows.

[0139] In this regard, the following equations (4A), (4B), and... Figure 2 To illustrate.

[0140] Equation (4A) is an equation transformed from equation (4) with R1 replaced by R. Similarly, equation (5A) is an equation transformed from equation (5) with R0 replaced by R. Furthermore, when equations (4A) and (5A) are shown together with the aforementioned equations (1A) and (2A) in the figure, as follows... Figure 2 As shown.

[0141] R=-0.0046×λ+9.1(500≤λ≤780)···(4A)

[0142] R=-0.0025×λ+6.5(500≤λ≤780)···(5A)

[0143] The following is a speculation: Figure 2 As shown, in the region with wavelength λ of 500 to 780 nm, i.e. the region from green to blue, by making the reflectivity R1 of the laser-processed position show a value on or higher than the line of Equation (4A), and making the reflectivity R0 of the un-laser-processed position show a value on or lower than the line of Equation (5A), the contrast of the color of this region is improved when viewed, thereby improving the visual recognition of the laser-processed position.

[0144] In addition, a * Corresponding to the position between red and green, negative values ​​correspond to a bias towards green, and positive values ​​correspond to a bias towards red. Since this disclosure satisfies the above equation (6), therefore the laser processing position a * (a * 1) a relative to the un-laser-processed position* (a * The difference of 0) (│a * 1-a * 0│) small. Therefore, it is speculated that visual recognition is improved by cooperating with green and red wavelengths, especially red wavelength. It should be noted that since the cooperation with red wavelength has little impact on visual recognition compared with yellow wavelength, it is speculated that satisfying equation (6) is an optional requirement, while equation (3) is a necessary requirement. It is speculated that by satisfying equation (3), the influence of a is prevented. * The difference (│a * 1-a * The influence of 0│) improves visual recognizability.

[0145] The reflectivity R1 at a wavelength of 580 nm can be 6.5%–8.0%. When the reflectivity R1 is above 6.5%, the contrast between the laser-processed and unprocessed areas becomes good. When the reflectivity R1 is below 8.0%, the decrease in visual recognition caused by diffuse reflection of transmitted light by the filler can be reduced. From this perspective, the reflectivity R1 can be 6.5%–7.9%.

[0146] The reflectance R0 at a wavelength of 580 nm can be 3.5% to 6.0%. When the reflectance R0 is 3.5% or higher, the cured resin molded product has general brightness, and when the reflectance R0 is 6.0% or lower, the decrease in contrast with the laser marking area can be reduced.

[0147] The difference |R1-R0| between the reflectance R1 and the reflectance R0 can be 1% to 7%. When the difference |R1-R0| is 1% or more, the contrast with the laser-marked portion becomes sufficient; when the difference |R1-R0| is 7% or less, it is within the general chromaticity range of the cured resin composition. From this viewpoint, the difference |R1-R0| can be 1.5% to 5.0%, or 2.0% to 4.0%.

[0148] ΔL * Defined as follows, ΔL * It can be 0 to 3.

[0149] ΔL * =│L * 1-L * 0│

[0150] When the above ΔL * When the value is below 1, the decrease in visual recognition caused by diffuse reflection of transmitted light due to filler can be reduced. From this perspective, ΔL * It can be below 2.5, below 2.0, or below 0.5.

[0151] It should be noted that in the range of 500≤λ≤780, using a combination of resins with high brightness tends to decrease the R1 value, while using resins with moderate brightness (specifically, L) * Combinations of resins with a content of approximately 60 or less tend to have an increasing R1 value. Furthermore, in the range of 500 ≤ λ ≤ 780, increasing the amount of colorant tends to decrease the R0 value, while decreasing the amount of colorant tends to increase the R0 value. Additionally, the brightness L of the combined raw materials themselves... * For components between approximately 50 and 60, there is a tendency for the value of R1 minus R0 (R1-R0) to decrease; outside this range, there is a tendency for the value of R1 minus R0 (R1-R0) to increase. This is achieved by decreasing a. * The absolute value of 2, having the a * The difference (│a * 1-a * The tendency of 0│) to decrease, by increasing a * The absolute value of 2, having the a * The difference (│a * 1-a * 0│) tends to increase.

[0152] The coefficient of linear expansion (ppm / ℃) of the cured material below the glass transition temperature is denoted as CTE1, and the coefficient of linear expansion (ppm / ℃) of the cured material above the glass transition temperature is denoted as CTE2.

[0153] The CTE1 can be 8–20 ppm / ℃, or 9–18 ppm / ℃. Within this range, warpage can be reduced.

[0154] The CTE2 can be 30–70 ppm / ℃, 35–60 ppm / ℃, 40–55 ppm / ℃, or 43–53 ppm / ℃. Within this range, warpage can be reduced.

[0155] From the viewpoint of improving formability, the glass transition temperature of the cured material is above 110°C, and from the viewpoint of warping during molding, it is below 200°C. From this perspective, it can be 120–180°C or 130–150°C.

[0156] The glass transition temperature (Tg) mentioned above can be determined by thermomechanical analysis (TMA), specifically by the method described in the examples.

[0157] Semiconductor Devices

[0158] Next, the semiconductor device of this disclosure will be described.

[0159] In the semiconductor device disclosed herein, the semiconductor element is sealed by the aforementioned resin composition.

[0160] Figure 3 This is a cross-sectional view illustrating an example of the configuration of the semiconductor device of this disclosure.

[0161] The semiconductor device has the following structure: a semiconductor element 1 is provided on a substrate 4 with solder balls 5 on the back side via bumps 3, and a sealing material 2 made of the aforementioned cured material is provided between the semiconductor element 1 and the bumps 3 and around them (side surface, top surface).

[0162] Solder balls 5 are used as terminals for connecting to the wiring board, and bumps 3 are used to connect semiconductor element 1 and wiring formed on substrate 4.

[0163] <Methods for Manufacturing Semiconductor Devices>

[0164] The semiconductor device of the present invention can be manufactured using the aforementioned resin composition by means of transfer molding, compression molding, sheet molding, etc., as shown below.

[0165] When using tablet-shaped resin compositions, they can be manufactured at a sealing temperature between 150 and 250°C using known molding methods such as conventional transfer molding.

[0166] When using a powdered resin composition, it is manufactured as follows.

[0167] First, a substrate with a semiconductor element mounted on it is supplied to the upper mold of the molding die, and the powdered resin composition of this disclosure is supplied to the lower mold cavity. Next, the upper and lower molds are closed by applying a required closing pressure, immersing the semiconductor element in the heated and molten resin composition within the lower mold cavity. Thereafter, the heated and molten resin composition within the lower mold cavity is pressed down by a cavity bottom member, and the required pressure is applied under reduced pressure to perform compression molding. The preferred molding conditions are a temperature of 120–200°C and a pressure of 2–20 MPa. By compression molding under these conditions, the semiconductor device of this disclosure can be obtained.

[0168] When using a sheet resin composition, for example, by mounting a semiconductor element mounted on a substrate into the cavity of an upper and lower mold, after placing the sheet resin composition, using a press to close the upper and lower molds, and heating while applying pressure to cure the sheet resin composition, the semiconductor device of this disclosure can be obtained.

[0169] The semiconductor devices disclosed herein are not particularly limited to semiconductor elements, such as integrated circuits, large-scale integrated circuits, transistors, thyristors, diodes, solid-state imaging elements, AP (Application Processor) or GPU (Graphics Processing Unit).

[0170] Example

[0171] Next, the present invention will be specifically described through examples, but the present invention is not limited to these examples.

[0172] (Examples 1-3 and Comparative Examples 1-4)

[0173] A resin composition was prepared by mixing the components of the types and amounts listed in Table 1 using a twin-screw extruder at a mixing temperature of 100°C and a mixing time of 5 minutes.

[0174] It should be noted that in Table 1, blank columns indicate no cooperation.

[0175] The specific components listed in Table 1 used in the preparation of the resin composition are as follows.

[0176] (A) Thermosetting resin

[0177] YX-4000HK: Biphenyl-type epoxy resin (trade name, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 180, softening point: 107℃).

[0178] NC-3000: Biphenyl phenolic varnish epoxy resin (trade name, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 273, softening point 58℃).

[0179] ·EPPN-502H: Triphenylmethane type epoxy resin, manufactured by Nippon Kayaku Co., Ltd., trade name, epoxy equivalent 168, softening point 67℃.

[0180] (B) Curing agent

[0181] MEHC-7851-SS: A phenolic aralkyl resin containing a biphenyl backbone, trade name, manufactured by Meiwa Chemical Co., Ltd., with a hydroxyl equivalent of 203 and a softening point of 66°C.

[0182] MEHC-7800SS: Aryl alkyl phenolic resin, trade name, manufactured by Meiwa Kasei Corporation, hydroxyl equivalent 172, softening point 65℃.

[0183] MEH-7500: Triphenylmethane-type phenolic resin, trade name, manufactured by Meiwa Kasei Corporation, hydroxyl equivalent 97, softening point 110℃.

[0184] ·MF-1M: Cresol-type phenolic resin, trade name, manufactured by Meiwa Kasei Corporation, hydroxyl equivalent 106, softening point 86℃.

[0185] [(C) Inorganic packing]

[0186] •FB-105FC: Spherical fused silica, trade name, manufactured by Denka Co., Ltd., average particle size 11.9μm.

[0187] ·SC-4500SQ: Spherical fused silica, trade name, manufactured by ADMATECHS CO.,LTD., with an average particle size of 1μm.

[0188] •FB-940: Spherical fused silica, trade name, manufactured by Denka Co., Ltd., average particle size 15.2μm.

[0189] ·MUF-46: Spherical fused silica, trade name, manufactured by Ryusen Co., Ltd., average particle size 4μm.

[0190] (D) Curing accelerator

[0191] •TIC-188: Imidazole inclusion complex (trade name, manufactured by Nippon Soda Co., Ltd.)

[0192] ·2P4MHZ-PW: 2-Phenylon-4-methyl-5-hydroxymethylimidazolium, manufactured by Shikoku Chemical Industry Co., Ltd., trade name (reaction start temperature with bisphenol A type epoxy resin: 129°C).

[0193] [(E) Coloring agent]

[0194] ·Tilack-D TM-B: Titanium black, trade name, manufactured by Akaho Chemicals Co., Ltd.

[0195] MA-100RMJ: Carbon black, trade name, manufactured by Mitsubishi Chemical Company.

[0196] [Other ingredients]

[0197] • Release agent: Palm wax No. 1, trade name, manufactured by Toyo ADL Co., Ltd.

[0198] • Silane coupling agent: Y-9669 (trade name, Momentive, 3-(N-phenyl)aminopropyltrimethoxysilane).

[0199] The properties of the resin compositions prepared in Examples 1-3 and Comparative Examples 1-4 were measured and evaluated under the test conditions shown below. The evaluation results are shown in Table 1.

[0200] [Evaluation Items]

[0201] (1) Spiral flow

[0202] Spiral flow was measured by transferring the obtained resin composition under molding conditions of 175°C and 7 MPa.

[0203] (2) Gel time

[0204] On a hot plate maintained at 175°C, while the obtained resin composition is diffused into a circle with a diameter of 3-5 cm and kneaded at a constant speed, the time it takes for the resin composition to thicken and eventually lose viscosity is measured.

[0205] (3) Flow viscosity

[0206] The viscosity of the obtained resin composition was determined according to JIS K 7210:1999 using a high-performance flowability tester (manufactured by Shimadzu Corporation, product name: CFT-500C).

[0207] (4) Glass transition temperature (Tg) and coefficient of thermal expansion (CTE1, CTE2) of the cured product

[0208] The obtained resin composition was molded using a transfer molding machine at a mold temperature of 175°C, a molding pressure of 7 MPa, and a curing time of 120 seconds. The mixture was then further cured at 175°C for 8 hours to produce test specimens (3 mm × 4 mm × 17 mm). Using these test specimens, the TMA curves were measured in a thermal analysis apparatus (manufactured by Seiko Instruments Co., Ltd., product name: TMA / SS150) at a heating rate of 10°C / min and a load of 98 mN.

[0209] The slope of the tangent to the obtained TMA curve in the range of 40–90 °C is denoted as the coefficient of linear expansion CTE1, and the slope of the tangent to the obtained TMA curve in the range of 200–230 °C is denoted as the coefficient of linear expansion CTE2. In addition, the temperatures at which the TMA curves intersect the tangent at 90 °C and 190 °C are recorded, and these temperatures are denoted as the glass transition temperature (Tg).

[0210] (5) Reflectivity of solidified material

[0211] The obtained resin composition was molded using a transfer molding machine at a mold temperature of 175°C, a molding pressure of 7 MPa, and a curing time of 120 seconds. It was then further cured at 175°C for 8 hours to produce test pieces.

[0212] The surface of the test piece was irradiated with a laser under the following conditions.

[0213] • Device Name: Three-Dimensional Micro Laser Processing Device (OPTEC, Model: WS-Flex)

[0214] Laser wavelength: 532nm.

[0215] • Output: 20W.

[0216] • Pulse width: 15ps.

[0217] • Speed: 2000mm / s.

[0218] • Line width: 15μm.

[0219] • Maximum repetition frequency: 20MHz.

[0220] • Beam quality: M2 < 1.3.

[0221] For the laser-irradiated areas of the test piece, the reflectance R1 (%) was measured every 2 nm at wavelengths in the range of 400–800 nm using a spectrophotometer (Jasco, product name: V-670). The results are shown below. Figure 4 .

[0222] Similarly, for the un-laser-irradiated areas of the test piece, the reflectance R0 (%) was measured every 2 nm at wavelengths in the 400–800 nm range using a spectrophotometer (Jasco, product name: V-670). The results are shown below. Figure 5 .

[0223] (6) Color of the cured product

[0224] The obtained resin composition was molded using a transfer molding machine at a mold temperature of 175°C, a molding pressure of 7 MPa, and a curing time of 120 seconds. The mixture was then further cured at 175°C for 8 hours to produce test pieces.

[0225] For this test piece, an integrating sphere spectrophotometer (X-Rite, SP-62) was used to measure L five times according to JIS Z8781-4 (2013). * a * and b * The average value of each is denoted as the chromaticity coordinate (L). * 0, a * 0, b * 0).

[0226] The surface of the test piece was irradiated with laser under the following conditions.

[0227] • Device Name: Three-Dimensional Micro Laser Processing Device (OPTEC, Model: WS-Flex)

[0228] Laser wavelength: 532nm.

[0229] • Output: 20W.

[0230] • Pulse width: 15ps.

[0231] • Speed: 2000mm / s.

[0232] • Line width: 15μm.

[0233] • Maximum repetition frequency: 20MHz.

[0234] • Beam quality: M2 < 1.3.

[0235] For the laser-irradiated areas in the test piece, an integrating sphere spectrophotometer (X-Rite, SP-62) was used to measure L five times according to JIS Z8781-4 (2013). * a * and b * The average value of each is denoted as the chromaticity coordinate (L). * 1, a * 1, b * 1).

[0236] In addition, ΔL is calculated according to the following formula. * , Δa * and Δb * .

[0237] ΔL * =│L * 1-L * 0│

[0238] Δa * =│a * 1-a * 0│

[0239] Δb * =│b * 1-b * 0│

[0240] (7)(A) The color of the cured product of thermosetting resin and (B) curing agent

[0241] Epoxy resin (A) "YX-4000HK" was placed in an aluminum cup, melted and homogenized at approximately 100–150°C, and then air-cooled and cured. The cured material was then measured five times using an integrating sphere spectrophotometer (X-Rite, SP-62) according to JIS Z8781-4 (2013). * a * and b * The average value of each is denoted as the chromaticity coordinate (L). * raw a* raw b * raw ).

[0242] Similarly, the same operation was performed on (A) epoxy resin "NC-3000", (A) epoxy resin "EPPN-502H", (B) curing agent "MEHC-7851-SS", (B) curing agent "MEHC-7800SS", (B) curing agent "MEH-7500", and (B) curing agent "MF-1M", and the chromaticity coordinates were recorded as (L). * raw a * raw b * raw ).

[0243] Next, for each embodiment and comparative example, the L of each (A) epoxy resin was... * raw a * raw and b * raw And L of each (B) curing agent * raw a * raw and b * raw The weighted average value L according to the mix proportions shown in Table 1 * 2. a * 2 and b * 2 is denoted as the chromaticity coordinates (L) of the cured product of (A) thermosetting resin and (B) curing agent. * 2, a * 2, b * 2).

[0244] For example, in Example 1, the L of the cured product of (A) thermosetting resin and (B) curing agent was calculated as follows. * 2. a * 2 and b * 2.

[0245] ·L * 2 = {(YX-4000HK's L)} * raw ×2.40)+(NC-3000's L * raw ×5.90)+(MEHC-7800SS's L * raw ×5.80)} / (2.40+5.90+5.80)

[0246] ·a* 2 = {(YX-4000HK of a} * raw ×2.40)+(NC-3000 of a) * raw ×5.90)+(MEHC-7800SS of a * raw ×5.80)} / (2.40+5.90+5.80)

[0247] ·b * 2 = {(YX-4000HK of b} * raw ×2.40)+(NC-3000's b * raw ×5.90)+(MEHC-7800SS of b * raw ×5.80)} / (2.40+5.90+5.80)

[0248] (8) Visual recognizability of QR codes (registered trademarks) printed on solidified materials

[0249] The obtained resin composition was molded using a transfer molding machine at a mold temperature of 175°C, a molding pressure of 7 MPa, and a curing time of 120 seconds. The mixture was then further cured at 175°C for 8 hours to produce test pieces.

[0250] The surface of the test piece was laser-irradiated under the following conditions, and a QR code (registered trademark) was printed on it.

[0251] • Device Name: Three-Dimensional Micro Laser Processing Device (OPTEC, Model: WS-Flex)

[0252] Laser wavelength: 532nm.

[0253] • Output: 20W.

[0254] • Pulse width: 15ps.

[0255] • Speed: 2000mm / s.

[0256] • Line width: 15μm.

[0257] • Maximum repetition frequency: 20MHz.

[0258] • Beam quality: M2 < 1.3.

[0259] The QR code (registered trademark) was read using a QR code (registered trademark) reader (manufactured by JASCO, trade name V-670), and evaluated as follows. The results are shown in Table 1.

[0260] 〇: Can be read.

[0261] ×: Cannot be read.

[0262]

[0263]

[0264]

[0265] As shown in Table 1, since Examples 1 to 3 satisfy equations (1) to (3), the QR code (registered trademark) has good readability and therefore good visual recognition.

[0266] On the other hand, since Comparative Example 1 does not satisfy Equation (2), Comparative Example 2 does not satisfy Equation (1), Comparative Example 3 does not satisfy Equation (3), and Comparative Example 4 does not satisfy Equation (1) and Equation (2), the readability of the QR codes (registered trademarks) is poor, and therefore their visual recognition is poor.

Claims

1. A semiconductor device, wherein, A cured product comprising a substrate, a semiconductor element mounted on the substrate, and a resin composition sealing the semiconductor element. The resin composition comprises a thermosetting resin, a curing agent, and an inorganic filler. The reflectance of the un-laser-processed portion of the solidified surface at wavelength λ is denoted as R0. The colorimetric coordinates of the cured material, determined according to JIS Z8781-4:2013, were marked as ( 0, 0, 0) When the solidified material is laser-processed with a laser wavelength of 532nm, the reflectivity of the laser-processed location under the wavelength λ condition is denoted as R1. When laser processing is performed on the cured material using a laser wavelength of 532 nm, the laser processing position is marked according to the colorimetric coordinates determined by JIS Z8781-4:2013. 1, 1, 1) At that time, Satisfy the following equations (1) to (3). R1≥-0.0050×λ+9.3,450≤λ≤600 (1), R0≤-0.0047×λ+7.6,450≤λ≤600 (2), │ 1- 0│≤0.45 (3)。 2. The semiconductor device of claim 1, wherein, Satisfy the following equations (4) to (6). R1≥-0.0046×λ+9.1,500≤λ≤780 (4) R0≤-0.0025×λ+6.5,500≤λ≤780 (5), │ 1- 0│≤0.35 (6)。 3. The semiconductor device as claimed in claim 1, wherein, The reflectivity R1 at a wavelength of 580 nm is 6.5–8.0%.

4. The semiconductor device as claimed in claim 2, wherein, The reflectivity R1 at a wavelength of 580 nm is 6.5–8.0%.

5. The semiconductor device according to any one of claims 1 to 4, wherein, The colorimetric coordinates of the composition y, which consists only of a thermosetting resin and a curing agent, determined according to JIS Z8781-4:2013, are marked as follows: 2, 2, When 2), the following equations (7) and (8) are satisfied. │ 2│≤0.40 (7), │ 2│≤10.00 (8), The chromaticity coordinates of the composition y ( 2, 2, 2) Indicates: For cured products formed by melting and cooling each raw material classified as a thermosetting resin and curing agent, the chromaticity coordinates are determined according to JIS Z8781-4:2013. raw , raw , raw ), and according to the mass ratio of each raw material contained in the composition y, the chromaticity coordinates ( raw , raw , raw The chromaticity coordinates are obtained by weighted averaging.

Citation Information

Patent Citations

  • Sealing resin composition and electronic device using the same

    JP2020132750A

  • Resin composition for laser marking and laser marking method and molded article

    JP2003155414A

  • Sealing resin composition and semiconductor device using the same

    JP2005089645A